Bibliometric Review of the Literature on the Social and Solidarity Economy in the Areas of Economy, Econometry, Finance, Business, Management and Accounting - Gonzales-Torres, Xochitl Berenise; Cruz-Cabrera, Blasa Celerina; Méndez-Prada, Martha Cecilia; Acevedo-Martínez, Jorge Antonio (Unidad Editorial UPTC, 2023)
The objective of this article is to analyze the scientific production on the Social and Solidarity Economy (ESS) in the areas of economics, econometrics, finance, business, management and accounting; through the use of bibliometric techniques. The study is carried out in a period of 50 years, between 1971 and 2021, whose main source is the Scopus database; additionally, the information is analyzed using the VOSviewer software. The search yielded a total of 727 documents related to the field addressed, finding that the United States is the leading country in scientific production; 93 % of the works consulted were scientific articles, the topics related to the SSE are: solidarity, sustainability, microfinance, inequality, autonomy, social movements, cooperatives, social justice, gender, women, agroecology, and social responsibility. It is important to consider that scientific progress in all fields increases day by day, therefore, the data changes. It is concluded that it is essential to understand the processes related to the SSE in the mentioned areas, as it is a potential to develop economic activities based on values such as justice, equity, transparency, and cooperativism. JEL Codes: R1, A12, Y8, Z0 Received: 19/01/2023.  Accepted: 14/04/2023.  Published: 06/05/2023.